The Influence of Service Quality on Patient Satisfaction at the Hasanudin Damrah Manna Regional General Hospital, South Bengkulu Regency - Ahmad Pajri; Karona Cahya Susena; Sri Handayani (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The purpose of this study is to test whether there is an effect of service quality (X) on patient satisfaction (Y) at Hasanuddin Damrah Regional General Hospital Manna, South Bengkulu Regency, always tries to provide the best for all patients. This is to provide satisfaction for all patients at Hasanuddin Damrah Manna General Hospital, South Bengkulu Regency. This type of research used quantitative research. The sample used in this study was 80 patients from Hasanuddin Damrah Regional General Hospital Manna, South Bengkulu Regency. Data collection was carried out by distributing questionnaires. Data analysis used is validity, reliability, simple linear regression, normality, coefficient of determination, correlation coefficient, hypothesis testing. Based on the results of research on the effect of service quality on patient satisfaction at Hasanuddin Damrah Regional General Hospital Manna. So the following conclusions can be drawn: Simple linear regression analysis shows Y = 4,666 + 0,770 (X) this illustrates the positive regression direction. This means that there is a positive influence between Service Quality (X) on Patient Satisfaction (Y). This means that every variable of Service Quality increases, Patient Satisfaction will also increase. The results of the t test at a significant level of 0.05. on the table 4.10 it can be seen that t count (12,133) > T table (1,990), then the hypothesis is accepted explaining that the service quality variable shows a significant effect on service quality on patient satisfaction at Hasanuddin Damrah Regional General Hospital Manna. The value of the coefficient of determination is 0.645. this shows that the effect of service quality on patient satisfaction is 65.4% while the remaining 34.6% is influenced by other variables not examined in this study.